2020
DOI: 10.7762/cnr.2020.9.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High β-glucan Barley on Postprandial Blood Glucose and Insulin Levels in Type 2 Diabetic Patients

Abstract: The aim of our study was to investigate whether high β-glucan-containing barley (7.2 g per 100 g) improves postprandial plasma glucose levels and suppresses postprandial insulin levels during a meal tolerance test in type 2 diabetic patients. A meal tolerance test (500 kcal) was conducted using two types of test meals: a test meal with white rice (WR) alone (WR diet) and a test meal with WR mixed with 50% barley (BR diet) as staple food. The side dish was the same in the both meals. The changes in plasma gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…In the present study, we have revealed for the first time that barley consumption ameliorates the hepatic fibrosis and steatosis of a mouse model of T2DM. Barley has previous been reported to reduce postprandial hyperglycemia, an effect that is due to its substantial β-glucan content [ 37 ]. A previous study also demonstrated that a barley sprout extract reduces lipid accumulation in the liver of mice, thereby alleviating severe alcoholic steatohepatitis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have revealed for the first time that barley consumption ameliorates the hepatic fibrosis and steatosis of a mouse model of T2DM. Barley has previous been reported to reduce postprandial hyperglycemia, an effect that is due to its substantial β-glucan content [ 37 ]. A previous study also demonstrated that a barley sprout extract reduces lipid accumulation in the liver of mice, thereby alleviating severe alcoholic steatohepatitis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The morphological characteristics and features of hulless barley are similar to those of wheat, while it contains more healthy nutrients than wheat does, such as dietary fiber (11.70–12.96%), β-glucan (4.4–5.5%), polyphenol (2.71–4.37 mg·g −1 ), and flavonoids (0.56–2.86 mg·g −1 ) ( 5 , 6 ). A recent study showed that white rice supplemented with 50% high β-glucan (7.2%) barley can inhibit postprandial blood glucose and insulin levels in patients with type 2 diabetes ( 7 ). Intraperitoneal injection of β-glucan (400 and 800 mg/kg/day) could substantially reduce the mortality of X-ray whole-body irradiated mice and the tumor growth of tumor-bearing mice ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, due to precise and flexible dosage adjustment, the insulin pump can quickly control the blood glucose, reduce insulin dosage, and reduce the occurrence of hypoglycemia, which is an important means of intensive insulin therapy 4 . The impact of the diet on glycemic control but also on complications is really important 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, proinsulin can be decomposed into one molecule of insulin and one molecule of C-peptide. Thus, the molar weight of C-peptide is the same as that of a patient’s self-secreted insulin 5 . Furthermore, it is not easy for C-peptide to be degraded by the liver.…”
Section: Introductionmentioning
confidence: 99%